IN SILICO MODELLING, SYNTHESIS, AND ANTI-DIABETIC EVALUATION OF BENZOTHIAZOLE SUBSTITUTED OXADIAZOLE DERIVATIVES - VIJAYAN, MEENU; PT, MANJU; PN, LEYANA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The study contemplates in silico modeling, synthesis and in-vitro anti-diabetic evaluation of benzothiazole substituted oxadiazole derivatives. [{5-[(1, 3-benzothiazol-2-ylsulfanyl) methyl]-1, 3, 4-oxadiazol-2-yl} sulfanyl) methyl] derivatives were synthesized by a conventional method. Methods: All the newly synthesized derivatives were characterized by determining their melting point, retention factor from thin-layer chromatography, and spectral methods (Infrared, 1H NMR spectroscopy, 13C NMR spectroscopy, Mass spectroscopy) and evaluated for their anti-diabetic activity. Results: [{5-[(1, 3-benzothiazol-2-ylsulfanyl) methyl]-1, 3, 4-oxadiazol-2-yl} sulfanyl) methyl] derivatives have been made and characterized using physical and spectral methods. The in-vitro anti-diabetic screening study revealed that BZT1 and BZT4 exhibited high inhibition against glucose uptake assay and alpha-amylase enzyme. But only the derivative BZT4 showed inhibition against alpha-glucosidase enzyme. Conclusion: Various benzothiazole substituted oxadiazole derivatives were synthesized, characterized by spectral studies. The anti-diabetic studies revealed that the synthesized derivatives have significant anti-diabetic properties and further structure-activity relationship studies may develop more potent and less toxic molecules.